Socio-economic vulnerability and neo-liberalism lessons from Bangladesh - Rahman, Shahidur (© 2009 SAGE Publications, 2016)
This article was published in the South Asia Research journal [© 2009 SAGE publications] and the definite version is available at : http://dx.doi.org/10.1177/026272800902900303 The article website is at: http://sar.sagepub.com/content/29/3/235.abstract